Hematoimmunological responses of juvenile Nile tilapia (Oreochromis niloticus) receiving the dietary supplementation of immunomodulators and different levels of vitamins after challenge with physical stress - Costa, Domickson Silva; Dutra, Scheila Anelise Pereira; Pereira, Iracema Lima; Cardoso, Lucas; de Medeiros, Paula Brando; Riofrio, Liseth Vanessa Perenguez; Libanori, Maria Clara Miguel; Soligo, Tiago Augusto; Yamashita, Eduardo; Pereira, Ulisses de Pádua; Mourinõ, José Luiz Pedreira; Martins, Maurício L. (Brazilian Journal of Veterinary Medicine, 2024)
In this study, we analyzed the hematoimmunological effects of dietary supplementation with immunomodulators (β-glucans + nucleotides) and different levels of vitamins on Nile tilapia (Oreochromis niloticus) after exposure to physical stress. The following four diet treatments were used: diets with indicated vitamin levels (Vitind), diets with Vitind + immunomodulator (Vitind + Immune), diets with high vitamin content (Vithigh), and those with Vithigh + immunomodulator (Vithigh + Immune). The experiment included 560 fish in 28 tanks (20 fish tank-1), with seven replicates per treatment. After 60 days of supplementation, the water temperature was set at 20 °C, and complete biometrics were performed. The animals were then subjected to physical stress with temperature oscillations of 20 °C to 30 °C/30 °C to 20 °C/20 °C to 30 °C. Hematoimmunological data from 140 animals were collected poststress. Antimicrobial titer and total plasma protein levels were significantly higher in fish not receiving immunomodulator-supplemented diets (2.88 ± 0.43 log2 and 26.81 ± 4.01 mg∙mL-1, respectively) than in those that did. Conversely, the agglutination titer increased in fish fed with lower vitamin levels (3.33 ± 0.66 log2) compared to those with higher vitamin levels. Increased immunoglobulin levels were observed in fish fed diets co-supplemented with vitamins and immunomodulators, revealing an interaction between immunomodulators and dietary vitamin levels. In summary, the inclusion of immunomodulators in the diet enhanced the animals’ resistance to physical stress and improved hematoimmunological parameters. Additionally, a high vitamin content in the diet did not modulate the immune responses in the animals.